Evaluation of the Reliability and Validity of Actors' Vocal Hygiene Knowledge Questionnaire - Mohammad Ghorbani; Arezoo Hassanvand; Maryam Vahab; samaneh Hosseinzadeh (Shiraz University of Medical Sciences, 2019)
Background: One's voice is one of the most important tools for professional voice users, especially actors. Actors have limited knowledge of vocal hygiene that leads to vocal abuse and misuse of vocal behavior. For this reason, special care must be taken by this group in the form of vocal hygiene. Currently, no validated instrument determines knowledge levels of vocal hygiene education in actors as professional voice users. The "Assessment of actors' vocal hygiene knowledge" questionnaire is designed to measure actors' awareness of vocal hygiene. The purpose of this study was to investigate the validity and reliability of the "Assessment of actors' vocal hygiene knowledge". Methods This study was a methodological research that was conducted in two phases of designing and evaluating the validity and reliability of the "Assessment of actors' vocal hygiene knowledge" questionnaire. The participants in this study were 150 actors (91 men and 59 women) ranging in age from 18 to 45 years (mean age: 26.13 years and SD = 4.7). In this study, content validity ratio (CVR) and content validity index)CVI) was used to assess content validity. The reliability was examined using Cronbach's alpha and test-retest. Results: All test items had good content validity (CVR> 0.62 and CVI> 0.79). Cronbach's alpha coefficient for the whole test was 0.75. The questionnaire also had a high test-retest reliability including intra-class correlation coefficient) ICC (= 0.91 with 95% confidence interval. Conclusion: The results of this study indicate that the "Assessment of actors' vocal hygiene knowledge" questionnaire has good validity and reliability for actors.